2019
DOI: 10.1093/hmg/ddz007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation of the ER stress response ameliorates oculopharyngeal muscular dystrophy

Abstract: Oculopharyngeal muscular dystrophy (OPMD) is a rare late onset genetic disease leading to ptosis, dysphagia, and proximal limb muscles at later stages. A short abnormal (GCN) triplet expansion in the polyA-binding protein nuclear 1 (PABPN1) gene leads to PABPN1-containing aggregates in the muscles of OPMD patients. Here we demonstrate that treating mice with guanabenz acetate (GA), an FDA-approved antihypertensive drug, reduces the size and number of nuclear aggregates, improves muscle force, protects myofiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 77 publications
0
26
0
1
Order By: Relevance
“…This is in line with previous observations that showed that BCAAs and ALA, when individually administered, exert a potent anti-inflammatory effect in both exercised animal models and athletes [29,48], and that IL-6 release can be modulated by nutritional interventions in trained subjects, with either BCAAs or ALA reducing post-exercise levels of this cytokine by 40% [49]. The ability to control inflammatory response may also help to preserve the equilibrium of BCAAs metabolism, since inflammation and endoplasmic reticulum stress play a critical role in regulating BCAAs uptake in adipocytes and muscle tissue [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous observations that showed that BCAAs and ALA, when individually administered, exert a potent anti-inflammatory effect in both exercised animal models and athletes [29,48], and that IL-6 release can be modulated by nutritional interventions in trained subjects, with either BCAAs or ALA reducing post-exercise levels of this cytokine by 40% [49]. The ability to control inflammatory response may also help to preserve the equilibrium of BCAAs metabolism, since inflammation and endoplasmic reticulum stress play a critical role in regulating BCAAs uptake in adipocytes and muscle tissue [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the disease progression manifests as visible changes in muscle mass at 18 weeks of age in the model mice (Trollet et al, 2010). Recent efforts to ameliorate symptoms have focused on small molecule approaches to target protein aggregation and gene therapy approaches to correct the mutation (Malerba et al, 2017(Malerba et al, , 2019a. In our previous study we showed that the administration of the RK35 antibody counteracted the muscle atrophy and improved histopathological features of the disease (Harish et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…Whole muscle images (for laminin based fiber morphometry) or random fields (for PABPN1 and collagen immunostaining) were captured using a microscope (Zeiss, United Kingdom). For analysis of fiber morphometry, the median minimal feret's diameter from 1000 randomly selected fibers were determined for TA muscles for each individual animal analyzed (Harish et al, 2019;Malerba et al, 2019a). For picrosirius red staining, sections were air dried, fixed in PFA 4%, and stained in a 0.3% solution of Sirius red in saturated aqueous picric acid, followed by a treatment with 0.5% acetic acid.…”
Section: Histological and Immunohistochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this module, three edges (Jund-Fos, Fosb-Fosl2, Fosl1-Fosl2) are only identified by scLink. In addition, the network also contains a four-gene module involved in muscle regeneration [61,62] and a five-gene module which was shown to play roles in myoblast differentiation [63,64,65]. These two modules are also missed by the classic correlation approach.…”
Section: Sclink Identifies Cell-type-specific Gene Network From the mentioning
confidence: 99%